2019
DOI: 10.35772/ghm.2019.01017
|View full text |Cite
|
Sign up to set email alerts
|

National Action Plan on Antimicrobial Resistance (AMR) 2016-2020 and relevant activities in Japan

Abstract: includes "International Cooperation" as a unique 6th pillar additionally set in reference to the 5 pillars of the Global Action Plan, and a goal, strategy and countermeasures have been set for each area (Figure 1). Current status and challenges of antibiotic treatment in Japan The use of antibiotics in Japan is not particularly higher compared to that in Europe or the USA. However, in Japan oral antibiotics account for 92.4% of the total daily usage, and consists of third generation cephalosporins, macrolides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Similarly, Japan is focusing on measures against drug resistance. The Japanese government formulated a "National Action Plan on Antimicrobial Resistance" with one of its six objectives to promote research on antimicrobial resistance and research and development to prevent, diagnose and treat antimicrobial-resistant infections [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Japan is focusing on measures against drug resistance. The Japanese government formulated a "National Action Plan on Antimicrobial Resistance" with one of its six objectives to promote research on antimicrobial resistance and research and development to prevent, diagnose and treat antimicrobial-resistant infections [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Azuma et al [ 46 ] compared the concentration of antimicrobial residues in hospital effluent with that in STP effluent and found that the concentration in the former was low and that most of the antimicrobials in STP effluent were from outside the hospital. In Japan, oral antimicrobials prescribed for an outpatient account for 92.4% of the total antimicrobials used daily, and most of them are used inappropriately [ 80 ]. Therefore, to reduce the burden of antimicrobials on the environment, efforts should be made to ensure that patients use oral antimicrobials correctly and that new technologies and strategies to treat antimicrobial agents in STP are developed and introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have been presented indicating that fluoroquinolone prophylaxis is helpful for patients in whom FN was expected to occur for more than 7 days 35 , 36 , though resistance to Escherichia coli and Pseudomonas aeruginosa has been observed in association with that therapy. With the spread of antibiotic-resistant bacteria in medical treatment becoming a severe public health problem 35 , 37 , 38 , appropriate use of antimicrobial agents is required. Studies that evaluated fluoroquinolone prophylaxis efficacy have found that prevention of FN in high-risk patients has advantages for infectious complications and does not affect mortality 37 , 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%